UTILIZATION AND DEVELOPMENT OF HISTORICAL SITES FOR IMPROVING THE ECONOMY OF THE REGION - Andi Andi; Rudy Gunawan; Dwi Ananto K; Ahmad Fachrul Rozi; M Abdul M (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2020)
Palembang is one of the oldest cities in Indonesia, a historical city and a prominent city with the greatness of the Srivijaya kingdom. Various events have become important historical traces for the local community and the general public, one of which is historical sites. One of them is the Archaeological Park of the Sriwijaya Kingdom, where this historical site can be developed and utilized to increase the regional economy. The purpose of this research is to find out how to use and develop historical sites for the improvement of the regional economy. Data were collected through a qualitative approach by exploring and interviewing participants accompanied by a review of various literatures. The result of this research is that the local government and society are sustainable in maintaining, developing, and utilizing historical sites to improve the regional economy.